Dual Molecular Diagnosis of Microsporidia (Encephalitozoon hellem) Keratoconjunctivitis in an Immunocompetent Adult. Issue 2 (February 2021) - Ma, Kevin K.; Kinde, Benyam; Doan, Thuy; Jacobs, Deborah S.; Ong Tone, Stephan
Abstract : Purpose: To report a case of microsporidia ( Encephalitozoon hellem ) keratoconjunctivitis acquired through avian transmission in an immunocompetent adult, diagnosed by metagenomic deep sequencing (MDS), and confirmed by polymerase chain reaction. Methods: A case report. Results: An 18-year-old woman was referred with unilateral keratoconjunctivitis unresponsive to topical and systemic therapy after exposure to birdcage debris. Slit-lamp examination of the left eye revealed a follicular papillary reaction of the palpebral conjunctiva and multiple corneal punctate epithelial opacities that stained minimally with fluorescein. In vivo confocal microscopy revealed bright double-walled structures and smaller bright round structures in the superficial epithelial debris and epithelium. Molecular diagnosis with MDS of E. hellem was confirmed by polymerase chain reaction. Clinical resolution and normalization of in vivo confocal microscopy was observed after a 6-week course of topical azithromycin. The patient elected a 3-week course of topical voriconazole 1% for definitive antimicrosporidial treatment, with no evidence of persistent infection 1 month later. Conclusions: Microsporidial ( E. hellem ) keratoconjunctivitis can occur through avian transmission in immunocompetent hosts. Topical azithromycin may be effective against this pathogen. MDS has utility in the diagnosis of atypical keratoconjunctivitis.